FAMILY SUPPORTIVE GROUP INTERVENTIONS FOR SCHIZOPHRENIA PATIENTS AT RSJD DR SAMSI JACOBALIS - Alyasa, M Hafidh; Yuningsih, Yuyun (Politeknik Kesejahteraan Sosial Bandung, 2025)
This research study entitled